Synaptic Dysfunction in Prion Diseases: A Trafficking Problem? - Assunta Senatore; Elena Restelli; Roberto Chiesa (International Journal of Cell Biology)
Synaptic dysfunction is an important cause of neurological symptoms in prion diseases, a class of clinically heterogeneous neurodegenerative disorders caused by misfolding of the cellular prion protein (PrPC). Experimental data suggest that accumulation of misfolded PrPC in the endoplasmic reticulum (ER) may be crucial in synaptic failure, possibly because of the activation of the translational repression pathway of the unfolded protein response. Here, we report that this pathway is not operative in mouse models of genetic prion disease, consistent with our previous observation that ER stress is not involved. Building on our recent finding that ER retention of mutant PrPC impairs the secretory trafficking of calcium channels essential for synaptic function, we propose a model of pathogenicity in which intracellular retention of misfolded PrPC results in loss of function or gain of toxicity of PrPC-interacting proteins. This neurotoxic modality may also explain the phenotypic heterogeneity of prion diseases.